(untitled) (Asian Journal of Social Science Studies, 2022)
The domestic amusement equipment industry is developing rapidly. In the production and installation interpretation activities of imported amusement facilities, the translation of terms is very important. Combined with the author’s interpreting practice, the whole process of interpreting practice is studied and analyzed, and the corresponding terminology translation methods are proposed from the three links of pre-translation, translation and post-translation. The author analyzes the three major techniques of preparation before interpretation, the “four methods” during interpretation, and the summary after interpretation in the interpretation task of the amusement facility industry, forming a technical closed loop.